Rancang Bangun Sistem Informasi Pelaksanaan Proyek Akhir Sarjana dan Diploma Berbasis Web - Rizan, Okkita; supardi, supardi (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2017)
STMIK Atma Luhur is a college pioneer in organizing high education in computer in the province in Bangka Belitung island . At this time it has increased to use the techonology can make it easy to people in doing something especially in education. But final project in the form of thesis and final job implementation in STMIK Atma Luhur has not computerized completely, there is only one system of desktop based, it is not efective for the students. This method that is used in analysis and designing this system is an object – oriented method, where is in this method there are classes, methods, objects and messages that associated with information system that will be made and model which is use a waterfall model that include of analysis and designing. From the problems that were made a web based system to make it easy students to carry out the final project as a requirement of graduation study undergraduate and diplomaKeywords-Information System, Waterfall, Object Oriented